Aktivitas Cesium (137Cs) Di Perairan Hutan Mangrove Karangsong, Kabupaten Indramayu - Muslim Muslim; Wahyu Retno Prihatiningsih; Adhi Prasojo; Jarot Marwoto; Purwanto Purwanto (Jurnal Kelautan Tropis, 2019)
The mangrove forest in Karangsong-Indramayu has been selected as a central mangrove forest for western Indonesia, in addition to a marine ecotourism destination. This condition with more visitors stimulates increase in organic carbon content in this water, which has the ability to bind to polluting elements, such as heavy metals and radionuclides. The purpose of this study is to understand the factors that effect 137Cs levels activities in Karangsong waters of Indramayu. To understand which factors effect 137Cs levels, we collected water quality which has the ability to bind to polluting elements data including temperature, salinity, DO, pH, depth and current speed.  The result showed that the 137Cs activities ranged 0.07-1.01 mBq/L with an average of 0.589 mBq/L. This value is higher than 137Cs activities in ITF (Indonesian Through Flow) which had value 0.274 mBq/L.  The higher 137Cs activities in Karangsong waters were caused by the presence of mangrove forest that effect the high levels of organic carbon rather than water quality that show relative homogeny in all stations.Perairan pantai Karangsong, Kabupaten Indramayu telah dijadikan sebagai pusat mangrove di bagian barat Indonesia, disamping sebagai eko wisata bahari. Kondisi tersebut tentunya akan meningkatkan kandungan karbon organik di perairan tersebut yang mempunyai kemampuan kuat untuk mengikat unsur-unsur pencemar seperti logam berat dan radionuklida. Tujuan penelitian ini ingin mengetahui tingkat aktivitas 137Cs di perairan Karangsong, Indramayu. Untuk mengetahui faktor-faktor yang mempengaruhi tingkat aktivitas 137Cs  di  perairan Karangsong, maka dianalisa beberapa parameter kualitas air seperti suhu, salinitas, DO, pH, kedalaman dan kecepatan arus. Hasil analisa menunjukkan aktivitas 137Cs adalah 0,07-1,01 mBq/L, dengan nilai rata-rata 0,589 mBq/L. Nilai tersebut lebih tinggi dari nilai 137Cs di ARLINDO (Arus Lintas Indonesia) yang nilai rata-ratanya 0,274 mBq/L. Tingginya aktivitas 137Cs tersebut lebih dipengaruhi dari adanya hutan mangrove yang menyebabkan tingginya bahan karbon organik dari pada pengaruh kualitas perairan yang relatif seragam.